Pine has two glutamine synthetase paralogs, GS1b.1 and GS1b.2, exhibiting distinct biochemical properties - Valderrama-Martín, José Miguel; Ortigosa Peña, Francisco; Aledo-Ramos, Juan Carlos; Ávila-Sáez, Concepción; Cánovas-Ramos, Francisco Miguel; Cañas-Pendón, Rafael Antonio (Wiley, 2023)
The enzyme glutamine synthetase (EC 6.3.1.2) is mainly responsible for the incorporation of inorganic nitrogen into organic molecules in plants. In the present work, a pine (Pinus pinaster) GS1 (PpGS1b.2) gene was identified, showing a high sequence identity with the GS1b.1 gene previously characterized in conifers. Phylogenetic analysis revealed that the presence of PpGS1b.2 is restricted to the genera Pinus and Picea and is not found in other conifers. Gene expression data suggest a putative role of PpGS1b.2 in plant development, similar to other GS1b genes from angiosperms, suggesting evolutionary convergence. The characterization of GS1b.1 and GS1b.2 at the structural, physicochemical, and kinetic levels has shown differences even though they have high sequence homology. GS1b.2 had a lower optimum pH (6 vs. 6.5) and was less thermally stable than GS1b.1. GS1b.2 exhibited positive cooperativity for glutamate and substrate inhibition for ammonium. However, GS1b.1 exhibited substrate inhibition behavior for glutamate and ATP. Alterations in the kinetic characteristics produced by site-directed mutagenesis carried out in this work strongly suggest an implication of amino acids at positions 264 and 267 in the active center of pine GS1b.1 and GS1b.2 being involved in affinity toward ammonium. Therefore, the amino acid differences between GS1b.1 and GS1b.2 would support the functioning of both enzymes to meet distinct plant needs
Keywords: Bioquímica; Glutamina; Metabolismo; Biochemistry; Development; Glutamine synthetase; Kinetic parameters; Nitrogen metabolism; Physicochemical properties; Conifer; Pinus pinaster